2014
DOI: 10.3109/01480545.2014.981753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of histidine andn-acetylcysteine on experimental lesions induced by doxorubicin in sciatic nerve of rats

Abstract: In this study, the effect of separate and combined intraperitoneal (i.p.) injections of histidine and n-acetylcysteine were investigated on experimental damage induced by doxorubicin (DOX) in sciatic nerve of rats. DOX was i.p. injected at a dose of 4 mg/kg once weekly for four weeks. Histidine and n-acetylcysteine were i.p. injected at a same dose of 20 mg/kg. Cold and mechanical allodynia were recorded using acetone spray and von Frey filaments tests, respectively. The sciatic nerve damage was evaluated by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…To identify the most relevant pathways and elucidate the underlying mechanism of DRG neuron survival and regeneration post injury from the metabolic pathways in a global angle, Metaboanalyst (http://www.metaboanalyst.ca/) was utilized. The analysis results revealed that the primary disturbed pathways in DRG differential metabolites post sciatic nerve injury were ‘Histidine metabolism’, 34,35 ‘Pentose phosphate pathway’, 36,37 ‘Arginine and proline metabolism’, 38 and ‘Glycerolipid metabolism’ (6 h vs. 0 h) 17,39 ; ‘Histidine metabolism’, ‘Glycine, serine and threonine metabolism’, 40–42 ‘Taurine and hypotaurine metabolism’, 43 ‘beta‐Alanine metabolism’, 44–46 ‘Pantothenate and CoA biosynthesis’, 47 and ‘Nicotinate and nicotinamide metabolism’ (1 d vs. 0 h) 48 ; ‘Histidine metabolism’, ‘Glycine, serine and threonine metabolism’, ‘Alanine, aspartate and glutamate metabolism’, 49 and ‘Arginine and proline metabolism’ (4 d vs. 0 h) (Figure 4, Dataset S3). Among these differential metabolic pathways, “Histidine metabolism’ is the only one that was enriched at each time point (vs. 0 h) after injury.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the most relevant pathways and elucidate the underlying mechanism of DRG neuron survival and regeneration post injury from the metabolic pathways in a global angle, Metaboanalyst (http://www.metaboanalyst.ca/) was utilized. The analysis results revealed that the primary disturbed pathways in DRG differential metabolites post sciatic nerve injury were ‘Histidine metabolism’, 34,35 ‘Pentose phosphate pathway’, 36,37 ‘Arginine and proline metabolism’, 38 and ‘Glycerolipid metabolism’ (6 h vs. 0 h) 17,39 ; ‘Histidine metabolism’, ‘Glycine, serine and threonine metabolism’, 40–42 ‘Taurine and hypotaurine metabolism’, 43 ‘beta‐Alanine metabolism’, 44–46 ‘Pantothenate and CoA biosynthesis’, 47 and ‘Nicotinate and nicotinamide metabolism’ (1 d vs. 0 h) 48 ; ‘Histidine metabolism’, ‘Glycine, serine and threonine metabolism’, ‘Alanine, aspartate and glutamate metabolism’, 49 and ‘Arginine and proline metabolism’ (4 d vs. 0 h) (Figure 4, Dataset S3). Among these differential metabolic pathways, “Histidine metabolism’ is the only one that was enriched at each time point (vs. 0 h) after injury.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of antioxidative treatments on preventing platinum-induced neurotoxicity has been established in several studies [2,9,55]. Antioxidants such as N-acetylcysteine (NAC) [18] have been used to reduce this type of toxicity. NAC is the acetylated form of L-cysteine, which has a peripheral neuroprotective effect through free radical elimination activity; cysteine helps in the synthesis of glutathione which is a very important natural antioxidant [26].…”
Section: Introductionmentioning
confidence: 99%
“…Inverse correlations between the pre-treatment levels of histidine, phenylalanine and threonine, and the maximum ΔCIPN8 were observed, suggesting that these amino acids could potentially predict PN severity in these patients. In fact, as indicated by Sun et al [ 94 ], histidine is involved in the pathogenesis and inflammatory process of neuropathic pain [ 116 , 117 , 118 ]; phenylalanine precursors are implicated in the development of neurological conditions [ 119 , 120 ]; and threonine could cause glycine accumulation in the brain, affecting neurotransmitter balance [ 121 ]. This study highlights the enormous potential of PMx studies in the follow-up of BC patients.…”
Section: Resultsmentioning
confidence: 99%